HUBUNGAN TINGKAT STRES TERHADAP PENINGKATAN KADAR GULA DARAH PADA PASIEN DM TIPE II DI RSU. ROYAL PRIMA MEDAN - Nababan, Tiarnida; Kaban, Karmila Br; Nurhayati, Eva Latifah (Jurnal Keperawatan Priority, 2020)
Diabetes mellitus is the result of the interaction of genetic factors and environmental exposure. Genetic factors will determine the individuals susceptible to DM.Uncontrolled diabetes and over time cause serious damage to many systems of the body, especially the nerves and blood vessels. By 2014, 8.5% of adults 18 years and over have diabetes. By 2015, diabetes is a direct cause of 1.6 million deaths and by 2012 high blood glucose is the cause of 2.2 million other deaths. This study aims to determine the relationship of stress levels to elevated blood sugar levels in patients with type II DM in Royal Prima Hospytal Medan. The research design used is correlation (Correlation Study) with Cross Sectional approach. The sample of this research is patient of DM type II disease with sample number 67 respondent using chi-square statistic test. Based on chi-square statistic test can be obtained result of 0,04 that is <0,05 means smaller than value α = 0,05. Thus drawn conclusion there is a relationship of stress level to increase blood sugar levels in DM tipe II patients in Royal Prima Hospytal Medan. From the results of the study concluded that there is a relationship level of stress to elevated blood sugar levels in patients DM tipe II. Suggested to Royal Prima Hospytal Medan recommends that patients keep control of stress on natural problems and diseases in order not to lead to other forms of disease.